Development of Edmodo-Based E-learning on Newton’s Laws - Iis Hisna Husna Takiah; Wita Puzi Lestari; Linda Handayani; Rahmat Rizal (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The application of learning technology in the digital era, for example, the use of learning, has potential advantages to help educators and students achieve learning goals. Learning activities are still conventional and using less attractive learning media affect students' interest and learning motivation, so learning media are needed to increase motivation and help students to understand the material optimally. This study aims to determine the validity of Edmodo-based e-learning media in Newton's Law courses. This type of research is Research and Development (R&D) with a 4D research design (Define, Design, Development, and Disseminate). This research is limited to the development stage. The respondents of this study were two teachers who were subject experts and media experts. The study results show that Edmodo-based e-learning on Newton's Laws is due to the validity of the learning media. Subject expert validity is in the very good category, with a score of 4.77. Media expert validity is in the good category, with a score of 3.90. The results of this study have implications for the readiness of learning media to support the achievement of learning objectives in Newton's Laws subjects.